Childhood acquired heart diseases in Jos, north central Nigeria - Bode-Thomas, Fidelia (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: The patterns of childhood acquired heart diseases (AHD) vary in different parts of the world and may evolve over time. We aimed to compare the pattern of childhood AHD in our institution to the historical and contemporary patterns in other parts of the country, and to highlight possible regional differences and changes in trend. MATERIALS AND METHODS: Pediatric echocardiography records spanning a period of 10 years were reviewed. Echocardiography records of children with echocardiographic or irrefutable clinical diagnoses of AHD were identified and relevant data extracted from their records. RESULTS: One hundred and seventy five children were diagnosed with AHD during the period, including seven that had coexisting congenital heart disease (CHD). They were aged 4 weeks to 18 years (mean 9.84΁4.5 years) and comprised 80 (45.7%) males and 95 (54.3%) females. Rheumatic heart disease (RHD) was the cause of the AHD in 101 (58.0%) children, followed by dilated cardiomyopathy (33 cases, 18.9%) which was the most frequent AHD in younger (under 5 years) children. Other AHD encountered were cor pulmonale in 16 (9.1%), pericardial disease in 15 (8.6%), infective endocarditis in 8 (4.6%) and aortic aneurysms in 2 (1.1%) children. Only one case each of endomyocardial fibrosis (EMF) and Kawasaki Disease were seen during the period. CONCLUSIONS: The majority of childhood acquired heart diseases in our environment are still of infectious aeitology, with RHD remaining the most frequent, particularly in older children. Community-based screening and multicenter collaborative studies will help to better describe the pattern of AHD in our country. More vigorous pursuit of the Millennium development goals will contribute to reducing the burden of childhood acquired heart diseases in the country.